Skin single-cell transcriptomics reveals a core of sebaceous gland-relevant genes shared by mice and humans. - Thalheim, T.; Schneider, M. R. (BMC Genomics, 2024)
BACKGROUND: Single-cell RNA sequencing (scRNA-seq) has been widely applied to dissect cellular heterogeneity in normal and diseased skin. Sebaceous glands, essential skin components with established functions in maintaining skin integrity and emerging roles in systemic energy metabolism, have been largely neglected in scRNA-seq studies. METHODS: Departing from mouse and human skin scRNA-seq datasets, we identified gene sets expressed especially in sebaceous glands with the open-source R-package oposSOM. RESULTS: The identified gene sets included sebaceous gland-typical genes as Scd3, Mgst1, Cidea, Awat2 and KRT7. Surprisingly, however, there was not a single overlap among the 100 highest, exclusively in sebaceous glands expressed transcripts in mouse and human samples. Notably, both species share a common core of only 25 transcripts, including mitochondrial and peroxisomal genes involved in fatty acid, amino acid, and glucose processing, thus highlighting the intense metabolic rate of this gland. CONCLUSIONS: This study highlights intrinsic differences in sebaceous lipid synthesis between mice and humans, and indicates an important role for peroxisomal processes in this context. Our data also provides attractive starting points for experimentally addressing novel candidates regulating sebaceous gland homeostasis.
Keywords: Humans; Mice; Animals; *Sebaceous Glands/metabolism; *Skin/metabolism; Gene Expression Profiling; Homeostasis; Amino Acids/metabolism